Standardization Status of Immersive Video Coding - Wien, Mathias; Boyce, Jill M.; Stockhammer, Thomas; Peng, Wen-Hsiao (IEEE journal on emerging and selected topics in circuits and systems, 2019)
Based on increasing availability of capture and display devices dedicated to immersive media, coding, and transmission of these media has recently become a highest-priority subject of standardization. Different levels of immersiveness are defined with respect to an increasing degree of freedom in terms of movements of the observer within the immersive media scene. The level ranges from three degrees of freedom allowing the user to look around in all directions from a fixed point of view to six degrees of freedom, where the user can freely alter the viewpoint within the immersive media scene. The moving pictures experts group (MPEG) of ISO/IEC is developing a standards suite on "Coded Representation of Immersive Media," called MPEG-I, to provide technical solutions for building blocks of the media transmission chain, ranging from architecture, systems tools, coding of video and audio signals, to point clouds and timed text. In this paper, an overview on recent and ongoing standardization efforts in this area is presented. While some specifications, such as high efficiency video coding or version 1 of the omnidirectional media format, are already available, other activities are under development or in the exploration phase. This paper addresses the status of these efforts with a focus on video signals, indicates the development timelines, summarizes the main technical details, and provides pointers to further points of reference.